2014
DOI: 10.1194/jlr.m047126
|View full text |Cite
|
Sign up to set email alerts
|

The caveolin-binding motif of the pathogen-related yeast protein Pry1, a member of the CAP protein superfamily, is required for in vivo export of cholesteryl acetate

Abstract: including immune defense in mammals and plants, pathogen virulence, sperm maturation and fertilization, venom toxicity, and prostate and brain cancer. Named after the founding members of this protein superfamily (cysteine-rich secretory protein, antigen 5, and pathogenesis-related 1), the CAP superfamily comprises more than 4,500 members in over 1,500 species, and family members are present in all kingdoms of life. Almost all CAP proteins are secreted glycoproteins and they are stable in the extracellular spac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
59
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(67 citation statements)
references
References 31 publications
7
59
0
1
Order By: Relevance
“…Our previous studies had revealed that the CBM is important for sterol binding of the yeast Pry1 protein (24). The hallmark of the CBM is the presence of aromatic amino acids in positions 1, 3, and 8 of the motif (øxøxxxxø) (24,28,29).…”
Section: Sequence Analysis Of the Caveolin-binding Motif Of Mppr-1 Prmentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous studies had revealed that the CBM is important for sterol binding of the yeast Pry1 protein (24). The hallmark of the CBM is the presence of aromatic amino acids in positions 1, 3, and 8 of the motif (øxøxxxxø) (24,28,29).…”
Section: Sequence Analysis Of the Caveolin-binding Motif Of Mppr-1 Prmentioning
confidence: 99%
“…Our previous studies had revealed that the CBM is important for sterol binding of the yeast Pry1 protein (24). The hallmark of the CBM is the presence of aromatic amino acids in positions 1, 3, and 8 of the motif (øxøxxxxø) (24,28,29). While the first aromatic residue is conserved in all MpPR-1 proteins, the aromatic residues at positions 3 and 8 of the motif are only conserved in MpPR-1c, MpPR-1d, MpPR-1g, and MpPR-1j, as revealed by the sequence alignment shown in Fig.…”
Section: Sequence Analysis Of the Caveolin-binding Motif Of Mppr-1 Prmentioning
confidence: 99%
See 2 more Smart Citations
“…Point mutations within this motif abrogate sterol export and binding while mutations of residues located outside the CBM had no effect on lipid export and binding. The CBM thus appears to play a key role in the ability of CAP proteins to bind cholesterol [5][6][7].…”
Section: Introductionmentioning
confidence: 99%